2019
DOI: 10.3390/ijms20133360
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Studies of Tissue Injury in Nonhuman Primates Exposed to Gamma-Radiation

Abstract: Exposure to ionizing radiation induces a complex cascade of systemic and tissue-specific responses that lead to functional impairment over time in the surviving population. However, due to the lack of predictive biomarkers of tissue injury, current methods for the management of survivors of radiation exposure episodes involve monitoring of individuals over time for the development of adverse clinical symptoms and death. Herein, we report on changes in metabolomic and lipidomic profiles in multiple tissues of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Following only one to two fractions of SBRT, higher plasma levels of the glycerophospholipids such as PC aa C30:0 and PC ae C30:0 were detected in the HCC patients with higher baseline CP score and ALBI grade compared to their lower score/grade counterparts, suggesting increased radiation-induced lipid turnover in the impaired livers. In line with our findings, some preclinical studies previously demonstrated significant dysregulation of various glycerophospholipids in the liver of non-human primates and rats at early (3 days) and late (60 days) time points following a single dose of whole body irradiation (which included the whole liver) compared to that of healthy controls who did not receive whole body irradiation [ 22 , 23 ]. Dysregulation of glycerophospholipids has also been reported in prostate cancer patients who developed urinary symptoms following prostate SBRT [24] .…”
Section: Discussionsupporting
confidence: 91%
“…Following only one to two fractions of SBRT, higher plasma levels of the glycerophospholipids such as PC aa C30:0 and PC ae C30:0 were detected in the HCC patients with higher baseline CP score and ALBI grade compared to their lower score/grade counterparts, suggesting increased radiation-induced lipid turnover in the impaired livers. In line with our findings, some preclinical studies previously demonstrated significant dysregulation of various glycerophospholipids in the liver of non-human primates and rats at early (3 days) and late (60 days) time points following a single dose of whole body irradiation (which included the whole liver) compared to that of healthy controls who did not receive whole body irradiation [ 22 , 23 ]. Dysregulation of glycerophospholipids has also been reported in prostate cancer patients who developed urinary symptoms following prostate SBRT [24] .…”
Section: Discussionsupporting
confidence: 91%
“…Proteomic profiling reports have included mouse and intestinal epithelial cell models (Bo et al 2005;Lim et al 2011;Huang et al 2019). More studies have focused on the complementary metabolome; metabolomic interrogation of intestine after radiation exposure has been reported for mouse, rat and NHP (Cheema et al 2014;Jang et al 2016;Cheema et al 2019a;Cheema et al 2019b;Jones et al 2019) and Kumar, Wang, et al in this issue. Additionally, a mass spectrometry imaging interrogation of the lipid alterations across the natural history of the PBI/BM2.5 model has been reported (Carter et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given this, the spleen is an important organ in fighting infections from bacteria and viruses [ 27 ], and, therefore, perturbations by exogenous genotoxic factors, such as ionizing radiation (IR), may lead to organ dysfunction. Data from low dose rate exposures [ 28 ] or high dose acute exposures [ 29 , 30 , 31 ] have shown significant effects on the spleen, including altered metabolism.…”
Section: Introductionmentioning
confidence: 99%